2021
DOI: 10.1039/d1cs00311a
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in visible light-activated radical coupling reactions triggered by (i) ruthenium, (ii) iridium and (iii) organic photoredox agents

Abstract: Visible light-activated reactions continue to expand and diversify. The example shown here is a Birch reduction achieved by organophotoredox reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
182
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 307 publications
(184 citation statements)
references
References 328 publications
(341 reference statements)
1
182
0
1
Order By: Relevance
“…However, two years later the same group revised their previous mechanism after detailed experimental spectroscopic and mechanistic investigations into the excited states of these Ni complexes [58] (Scheme 25). Through further experimental studies, the authors found that the previously computationally assigned 3 MLCT 1 state 137*, although generated upon excitation, decays to another long-lived state. This state was determined to be a tetrahedral 3…”
Section: Scheme 15 Photoinduced Sonogashira Cross-couplingmentioning
confidence: 99%
See 3 more Smart Citations
“…However, two years later the same group revised their previous mechanism after detailed experimental spectroscopic and mechanistic investigations into the excited states of these Ni complexes [58] (Scheme 25). Through further experimental studies, the authors found that the previously computationally assigned 3 MLCT 1 state 137*, although generated upon excitation, decays to another long-lived state. This state was determined to be a tetrahedral 3…”
Section: Scheme 15 Photoinduced Sonogashira Cross-couplingmentioning
confidence: 99%
“…Through further experimental studies, the authors found that the previously computationally assigned 3 MLCT 1 state 137*, although generated upon excitation, decays to another long-lived state. This state was determined to be a tetrahedral 3…”
Section: Scheme 15 Photoinduced Sonogashira Cross-couplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Radical reactions constitute a rapidly developing branch of synthetic organic chemistry [1]. The advent of photocatalysis has offered novel opportunities in radical chemistry, primarily associated with methods for the generation of radical intermediates [2][3][4]. Recently, we described an approach for the direct generation of free radicals from aliphatic thiols via their in situ conversion into zinc thiolates with subsequent abstraction of the sulfur by triphenylphosphine [5] (Scheme 1) The key idea of this method is that a combination of a thiolate and a phosphorus (III) reagent upon photoredox oxidation leads to a free radical and the strong phosphorus-sulfur double bond.…”
Section: Introductionmentioning
confidence: 99%